Architectural specification, exploration and simulation through rewriting-logic - Ayala-Rincón, Mauricio (2002)
In recent years Arvind’s Group at MIT has shown the usefulness of term rewriting theory for the speciﬁcation of processor architectures. In their approach processors speciﬁed by term rewriting systems are translated into a standard hardware description language for simulation purposes. In this work we present our current investigation on the use of Rewriting-Logic, which is a more powerful theoretical framework than pure rewriting, for speciﬁcation, exploration and veriﬁcation of processor architectures at a higher abstraction level. We adopt the rewriting-logic environment ELAN to specify, explore and verify architectures without the need to resort to the details of hardware description languages for simulation purposes. Our investigation shows that simulation at rewriting-logic level may provide useful insights to guide the architectural design.